Analisis Kesadaran Masyarakat Terhadap Bahaya Internet Phishing Menggunakan K-Means Clustering - Saputro, Indrawan Ady; Sugiarto, Lilik; Nugraha, Febrianta Surya (Universitas Indraprasta PGRI Jakarta, 2024)
Phishing is a form of cybercrime that tricks users with fake messages containing malicious links or attachments, causing financial loss, identity theft, or system damage. High security awareness is necessary to avoid phishing. This research aims to analyze public awareness of the dangers of phishing on the internet using the k-means clustering method. The data was collected through an online survey of 30 respondents from various backgrounds and processed using the k-means clustering algorithm to generate groups based on awareness levels. The revealed that the majority of respondents had moderate security awareness of phishing: 17% had high awareness, 57% moderate, and 26% low. Factors affecting the awareness include age, education, occupation, internet use frequency, and information sources. Cluster evaluation using Silhouette Coefficient indicated that grouping with 3 clusters (value 0.44) was the most effective, compared to 2 clusters (value 0.37) and 4 clusters (value 0.36). This research provides insight into the variation in security awareness and the importance of increasing digital literacy to protect the public from phishing.